Environmental Awareness: An Advocacy of The Mahabharat - Magar, Narayan Bahadur (Literary Studies, 2020)
The sublimation or the deterioration of the Earth depends on how the humans act over the natural world. The Mahabharata, an ancient Sanskrit literary text, reveals a way to the modern human as to treat with the natural phenomena. The degraded environment of the present more or less depends on how the human takes the natural world. This paper uses the Mahabharata, an English translation by Kisari Mohan Ganguli to analyze the text from ecological perspective. The researcher envisions the human relationship with the natural world in the epic through the concept of spiritual ecology.